Long-term mortality among adults diagnosed with cancer during three decades in Finland - Katuwal, Sushmita; Pukkala, Eero; Artama, Miia; Männistö, Satu; Tuomilehto, Jaakko; Jousilahti, Pekka (Frontiers in Cancer Control and Society, 2023)
Introduction This study aimed to determine all-cause and cause-specific mortality and, their time trends among adults with cancer, particularly among those who survived at least 5 years after cancer diagnosis, in comparison with mortality in the general population of the same age and sex. Methods The data on people with cancer were obtained from Finnish Cancer Registry and their underlying causes of death was obtained from Statistics Finland. All-cause and cause-specific standardized mortality ratios (SMR) and their 95% confidence intervals (CIs) were calculated for 327,585 people with cancer diagnosed between 1971 and 2000 and followed up until December 2012, stratified by decade and age of cancer diagnosis, sex, and type of cancer. Results In the working age (25–64 years), 50% of men and 74% of women diagnosed during 1991–2000 were alive 5 years of diagnosis; the corresponding proportions during 1971–1980 were 29 and 54%. Among the elderly people (65–74 years), corresponding proportions were 40 and 49%, and 19 and 32% in men and women, respectively. During the follow-up of 5–12 years, the all-cause SMR among working age people with cancer diagnosed 1971–2000 was 2.5 (95% CI 2.4–2.5) in men and 3.6 (95% CI 3.5–3.6) in women. A 20% excess mortality due to cardiovascular diseases was observed among working-age people in both sexes. Highest all-cause SMRs were observed among working age people with lung cancer in 1991–2000 (men 5.1, 95% CI 4.5–5.8: women 8.1, 95% CI 6.5–11). People diagnosed with cancer at an adult age in Finland have higher SMR in the follow-up category of 5–11.9 years but the absolute excess mortality for all calendar periods 1971–2000 combined in the older age category (3,448 per 100,000) is higher than in the younger category (2,247 per 100,000). Discussion Although the primary cause of death among cancer patients is cancer itself, increased SMRs of other conditions such as infections could indicate possible effect of cancer treatments as well as presence of shared risk factors among these diseases.